Liver transplantation for hepatocellular carcinoma: Historical evolution - Ince, V; Sahin, TT; Akbulut, S; Yilmaz, S (2022)
Liver transplantation (LT) for hepatocellular carcinoma is still a hot topic, and the main factor that is associated with the success of treatment is to determine the patients who will benefit from LT. Milan criteria have been defined 25 years ago and still is being used for patient selection for LT. However, in living donor LT, the Milan criteria is being extended. Current criteria for patient selection do not only consider morphologic characteristics such as tumor size and number of tumor nodules but also biologic markers that show tumor aggressiveness is also being considered. In the present review article, we have summarized all the criteria and scoring systems regarding LT for hepatocellular carcinoma. All criteria have 5-year overall survival rates that were comparable to the Milan Criteria and ranged between 60%-85%. On the other hand, it was seen that the recurrence rates had increased as the Milan criteria were exceeded; the 5-year recurrence rates ranged between 4.9% to 39.9%. Treatment of hepatocellular carcinoma needs a multidisciplinary approach. Ideal selection criteria are yet to be discovered. The same is true for treatment modalities. The goal will be achieved by a harmonic interplay between basic science researchers and clinicians. C1 [Ince, Volkan; Sahin, Tevfik Tolga; Akbulut, Sami; Yilmaz, Sezai] Inonu Univ, Surg & Liver Transplant Inst, Fac Med, TR-44280 Malatya, Turkey. [Akbulut, Sami] Inonu Univ, Biostat & Med Informat, Fac Med, TR-44280 Malatya, Turkey. [Akbulut, Sami] Inonu Univ, Surg & Liver Transplant Inst, Fac Med, Elazig Yolu 10 Km, TR-44280 Malatya, Turkey. C3 Inonu University; Inonu University; Inonu University